In the Author's Hand: Holograph and Authorial Manuscripts in the Islamic Handwritten Tradition - Bauden, Frédéric; Franssen, Elise (Islamic History and Civilization, 2020)
In recent years, a growing interest in "oriental manuscripts" in all their aspects, including the extrinsic ones, has been observed. Research that focuses on holograph, autograph and authorial manuscripts in Arabic handwritten script has nevertheless been casual, although these manuscripts raise important and varied questions. The study of the working methods of authors from the past informs different disciplines: paleography, codicology, textual criticism, ecdotics, linguistics and intellectual history. In this volume nine contributions and case studies are gathered that address theoretical issues and convey different, disruptive perspectives. A particularly important subject of this book, so far rarely discussed in scientific literature, is the identification of an author's handwriting. Among the authors specifically dealt with in this volume one will find: al-Maqrīzī (m. 845/1442), al-Nuwayrī (m. 733/1333), Akmal al-Dīn b. Mufliḥ (m. 1011/1603), al-ʿAynī (m. 855/1451) and Ibn Khaldūn (m. 808/1406). Contributors: Frédéric Bauden, Julien Dufour, Élise Franssen, Adam Gacek, Retsu Hashizume, Marie-Hélène Marganne, Elias Muhanna, Nobutaka Nakamachi, Anne Regourd, and Kristina Richardson.